2016
DOI: 10.1080/07388551.2016.1212185
|View full text |Cite
|
Sign up to set email alerts
|

Transport and transcriptional regulation of oil production in plants

Abstract: Triacylglycerol (TAG) serves as an energy reservoir and phospholipids as build blocks of biomembrane to support plant life. They also provide human with foods and nutrients. Multi-compartmentalized biosynthesis, trafficking or cross-membrane transport of lipid intermediates or precursors and their regulatory mechanisms are not fully understood. Recent progress has aided our understanding of how fatty acids (FAs) and phospholipids are transported between the chloroplast, the cytoplasm, and the endoplasmic retic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 107 publications
(159 reference statements)
1
73
0
Order By: Relevance
“…Regulation of oil biosynthesis by transcription factors (TFs) has been widely investigated and many transcription factors have been reported to affect TAG production [ 34 ]. Leafy cotyledon 1 ( LEC1 ) and LEC1-LIKE ( L1L ) TFs have been reported to regulate fatty acid synthesis through ACCase in Arabidopsis , maize and bean.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regulation of oil biosynthesis by transcription factors (TFs) has been widely investigated and many transcription factors have been reported to affect TAG production [ 34 ]. Leafy cotyledon 1 ( LEC1 ) and LEC1-LIKE ( L1L ) TFs have been reported to regulate fatty acid synthesis through ACCase in Arabidopsis , maize and bean.…”
Section: Introductionmentioning
confidence: 99%
“…DOF4 and DOF11 TFs were found to regulate fatty acid synthesis through ACCase, ENR and KASII in Arabidopsis and soybean. MYB73 was reported to regulate fatty acid synthesis through FATB and KAS genes in Arabidopsis and Camelina sativa [ 34 ]. However, WRINKLED1 ( WRI1 ) transcription factor is vital to synthesis, and is the “master regulator” of the transcriptional control of the plant oil biosynthesis pathway [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, proper maintenance and regulation of lipid metabolism is not only crucial for membrane function but also essential for plant development, growth and performance. Plant lipid metabolism therefore has been subjected to intensive studies and found to involve hundreds of enzymatic reactions, occurring in several subcellular compartments [5,6]. In turn, this requires exchange of FAs, lipids and their metabolic intermediates between organelles and membrane systems.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, proper maintenance and regulation of FA/lipid metabolism is not only crucial for membrane function but also essential for development, growth and fitness of organisms. Lipid metabolism therefore has been subjected to intensive studies and was found to involve hundreds of enzymatic reactions, occurring in several subcellular compartments (Li-Beisson et al 2013;Manan et al 2017;Tatsuta et al 2014). In turn, this requires exchange of FAs, lipids and their metabolic intermediates between organelles and membrane systems.…”
Section: Fax Proteins: Fatty Acid/lipid Transport By Membrane-bending?mentioning
confidence: 99%